Legal Analysis of 3 kg LPG Sales above The Het: A Corporate Social Responsibility and Good Governance Perspective - Nabila Rahmawati; Diana Setiawati (Universitas Muhammadiyah Surakarta, 2025)
Indonesia is blessed with a wealth of natural resources, including 3 kilograms (kg) LPG that is vital for household energy. However, the violation of the Highest Retail Price (HET) by bases harms low-income communities. Companies must comply with the law and implement sustainable business practices, ensure accessibility and community welfare, and enhance social responsibility and good governance. The purpose of this study is to determine the sale of 3 kg LPG above the Highest Retail Price as well as the responsibility and good governance by the company towards the sale of LPG above the Highest Retail Price. This research method uses a normative approach with a descriptive type to describe the sale of 3 kg LPG above the Highest Retail Price and corporate social responsibility. Data sources include secondary data from literature studies, including relevant regulations and laws, as well as journal articles. Data collection methods were conducted through literature study and qualitative data analysis. The results found that violations of the Highest Retail Price in the sale of 3 kg LPG by bases harm low-income communities, indicating difficulties in establishing fair and transparent distribution. Therefore, corporate social responsibility and good governance are needed to improve price transparency and distribution oversight for the welfare of the community and to ensure that government subsidy schemes are properly implemented. In conclusion, corporate social responsibility in the sale of 3-kg LPG includes accessibility for the community, especially the underprivileged, as well as consumer education on pricing and the risks of inappropriate sales practices.